2007
DOI: 10.1016/j.ijgo.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for placenta previa in an Asian population

Abstract: The risk factors for placenta previa were found to be the same for Asian women as those previously recorded for American and European women, but additional factors were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
5
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 24 publications
5
52
5
2
Order By: Relevance
“…After adj ustment cesarean section at first birth remained associated with increased risk of placenta previa (OR 1.6 95% CI 1.44-1.76).12 Previous history of abortions (both spontaneous and induced) have been significantly associated with up to three times risk of placenta previa. 2,4,13,14 In population based retrospective cohort study in Nova Scotia, Canada from 1988-1995, 308 cases of placenta previa were identified. Maternal complications included postpartum bleeding (RR-1.86), hysterectomy (RR-33.26), blood transfusion (RR-10.05), septicemia (RR-5.55).…”
Section: Discussionmentioning
confidence: 99%
“…After adj ustment cesarean section at first birth remained associated with increased risk of placenta previa (OR 1.6 95% CI 1.44-1.76).12 Previous history of abortions (both spontaneous and induced) have been significantly associated with up to three times risk of placenta previa. 2,4,13,14 In population based retrospective cohort study in Nova Scotia, Canada from 1988-1995, 308 cases of placenta previa were identified. Maternal complications included postpartum bleeding (RR-1.86), hysterectomy (RR-33.26), blood transfusion (RR-10.05), septicemia (RR-5.55).…”
Section: Discussionmentioning
confidence: 99%
“…1 Almost 30 % maternal deaths in the Asian population are due to major obstetrical haemorrhage in placenta previa, especially due to rise in the incidence of cesearean sections. 2 Significant maternal morbidity in the form of increased incidence of fetalmalpresentation, cesearean delivery, increased blood loss and peripartum hysterectomy have been noted in cases of placenta previa and can lead to prolonged hospitalization in these women.…”
Section: Introductionmentioning
confidence: 99%
“…Hung et al which was done in 457 patients with placenta previa in Asian population, 11.4% patients with placenta previa had history of previous cesarean done. 4 Authors can associate this finding with defects caused by previous scarring in the endometrium by previous CS. 5 The majority of the previa in present study were posterior (53 %), which was similar to the study of BC Young et al who studied 285 cases of placenta previa and found that 69% had posterior placenta previa, as evidence also suggests persistence of low lying posterior previa due to less expansion of the posterior wall compared with the anterior uterine wall.…”
Section: Discussionmentioning
confidence: 83%